Development of sustain release matrix tablet of ranolazine based on methocel K4M CR: In vitro drug release and kinetic approach - Asaduzzaman, Md.; Rahman, Md. Rezowanur; Rahman Khan, Md. Saifur; Islam, S.M. Ashraful (© 2011 Journal of Applied Pharmaceutical Science, 2016)
This article was published in the Journal of Applied Pharmaceutical Science [© 2011 Journal of Applied Pharmaceutical Science]